Pemberdayaan Modal Sosial Dalam Manajemen Pembiayaan Sekolah - Adi Dewanto; Rahmania Utari (Universitas Negeri Yogyakarta, 2006)
One of the strategies of educational finance management is how to be supported by society or the stakeholders of school. Through many experiences of how society has helped the development of its countries, it is realized that social capital is an important thing to be identified and managed by school. There are some aspects of social capital which can be informed to helping the management of school finance, and some ways to linking the society into being helpful community to create sufficient finance and arrangement of budgeting in school. Moreover, it is necessary to improve the leadership skill and relationship ability of the principal.